The Value and Credit Relevance of Multiemployer Pension Plan Obligations - Chen, Ting; Martin, Xiumin; Mashruwala, Christina A.; Mashruwala, Shamin D. (The Accounting Review, 2015)
ABSTRACT We investigate whether multiemployer defined-benefit pension plan (MEPP) underfunding is priced by shareholders and creditors. Prior to the FASB's new MEPP standard (effective December 2011), when the disclosures on such plans were sparse, we find evidence (some evidence) that our estimate of a firm's share of MEPP underfunding is credit (value) relevant. We also find some evidence that a proxy for the funded status of a firm's MEPPs is incrementally value relevant over and above the firm's cash contributions, but no evidence that it is credit relevant. Furthermore, an estimate of MEPP underfunding that incorporates the additional disclosures required under the new MEPP standard is value and credit relevant, both individually and incrementally, over and above our old estimate. Overall, our findings suggest that shareholders and creditors view MEPP underfunding as a debt-like obligation and that the additional MEPP disclosures under the new standard are useful to market participants.